2018
DOI: 10.1101/264747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency selective encoding of substrate vibrations in the somatosensory cortex

Abstract: Sensing vibrations that propagate through solid substrates conveys fundamental information about moving objects 6and other nearby dynamic events. Here we report that neurons responsive to substrate vibrations applied to the 7 mouse forelimb reveal a new way of representing frequency information in the primary somatosensory cortex (S1). In 8 contrast to vibrotactile stimulation of primate glabrous skin, which produces temporally entrained spiking and 9 frequency independent firing rates, we found that mouse S1 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…It is known that about 70–80% of rapidly adapting neurons in somatosensory cortex S1 show convergent inputs deriving from both afferent classes, and it may be that these neurons are responsible for this generalised frequency processing. Saal et al (2015) made an interesting observation that input from FAI afferents determines the cortical neuron response rate due to its net excitatory drive, while the more temporally-precise PC-channel has a balanced excitatory-inhibitory drive that can control the precise spike timing, which is useful in various encoding schemes (Birznieks and Vickery, 2017; Andrew Hires et al, 2015; Johansson and Birznieks, 2004; Prsa and Huber, 2018; Saal et al, 2016). This difference did not appear to affect frequency perception in the current study, as Weber fractions were found to be similar regardless of whether we used pulsatile stimuli exclusively activating FAII afferents in a time-controlled manner or used sinusoidal stimuli predominantly activating FAI afferents, presumably with less temporal precision due to the slow rising phase of the sinusoid.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that about 70–80% of rapidly adapting neurons in somatosensory cortex S1 show convergent inputs deriving from both afferent classes, and it may be that these neurons are responsible for this generalised frequency processing. Saal et al (2015) made an interesting observation that input from FAI afferents determines the cortical neuron response rate due to its net excitatory drive, while the more temporally-precise PC-channel has a balanced excitatory-inhibitory drive that can control the precise spike timing, which is useful in various encoding schemes (Birznieks and Vickery, 2017; Andrew Hires et al, 2015; Johansson and Birznieks, 2004; Prsa and Huber, 2018; Saal et al, 2016). This difference did not appear to affect frequency perception in the current study, as Weber fractions were found to be similar regardless of whether we used pulsatile stimuli exclusively activating FAII afferents in a time-controlled manner or used sinusoidal stimuli predominantly activating FAI afferents, presumably with less temporal precision due to the slow rising phase of the sinusoid.…”
Section: Discussionmentioning
confidence: 99%